The β3 Adrenergic Receptor Agonist CL316243 Ameliorates the Metabolic Abnormalities of High-Fat Diet-Fed Rats by Activating AMPK/PGC-1α Signaling in Skeletal Muscle - Ding LN (Dove Medical Press, 2021)
Li-Na Ding,1,* Ya Cheng,1,* Lu-Yao Xu,1 Le-Quan Zhou,1,2 Li Guan,1,2 Hai-Mei Liu,1,2 Ya-Xing Zhang,1,2 Run-Mei Li,1 Jin-Wen Xu1,2 1The Research Center of Basic Integrative Medicine, Basic Medical College, Guangzhou University of Chinese Medicine, University Town, Guangzhou, 510006, People’s Republic of China; 2Department of Physiology, Basic Medical College, Guangzhou University of Chinese Medicine, University Town, Guangzhou, 510006, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jin-Wen XuGuangzhou University of Chinese Medicine, University Town, Waihuan East Road 232, Guangzhou, 510006, People’s Republic of ChinaTel +86-20-39358028Fax +86-20-39358020Email xujinwen@gzucm.edu.cnPurpose: Skeletal muscle has a major influence on whole-body metabolic homeostasis. In the present study, we aimed to determine the metabolic effects of the β 3 adrenergic receptor agonist CL316243 (CL) in the skeletal muscle of high-fat diet-fed rats.Methods: Sprague-Dawley rats were randomly allocated to three groups, which were fed a control diet (C) or a high-fat diet (HF), and half of the latter were administered 1 mg/kg CL by gavage once weekly (HF+CL), for 12 weeks. At the end of this period, the serum lipid profile and glucose tolerance of the rats were evaluated. In addition, the phosphorylation and protein and mRNA expression of AMP-activated protein kinase (AMPK), peroxisome proliferator-activated receptor γ coactivator (PGC)-1α, and carnitine palmitoyl transferase (CPT)-1b in skeletal muscle were measured by Western blot analysis and qPCR. The direct effects of CL on the phosphorylation (p-) and expression of AMPK, PGC-1α, and CPT-1b were also evaluated by Western blotting and immunofluorescence in L6 myotubes.Results: CL administration ameliorated the abnormal lipid profile and glucose tolerance of the high-fat diet-fed rats. In addition, the expression of p-AMPK, PGC-1α, and CPT-1b in the soleus muscle was significantly increased by CL. CL (1 μM) also increased the protein expression of p-AMPK, PGC-1α, and CPT-1b in L6 myotubes. However, the effect of CL on PGC-1α protein expression was blocked by the AMPK antagonist compound C, which suggests that CL increases PGC-1α protein expression via AMPK.Conclusion: Activation of the β 3 adrenergic receptor in skeletal muscle ameliorates the metabolic abnormalities of high-fat diet-fed rats, at least in part via activation of the AMPK/PGC-1α pathway.Keywords: CL316243, AMPK, PGC-1α, L6 myotubes, carnitine palmitoyl transferase